2017
DOI: 10.1080/14740338.2018.1395854
|View full text |Cite
|
Sign up to set email alerts
|

Safety of pharmacotherapy options for bulimia nervosa and binge eating disorder

Abstract: Eating disorders represent a set of psychiatric illnesses with lifelong complications and high relapse rates. Individuals with eating disorders are often stigmatized and clinicians have a limited set of treatments options. Pharmacotherapy has the potential to improve long term compliance and patient commitment to treatment for eating disorders. Areas covered: This review will examine the efficacy and safety profile of the FDA-approved medications for the treatment of bulimia nervosa (BN) and binge eating disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 44 publications
1
16
0
4
Order By: Relevance
“…Presence of a comorbid anxiety disorder may weight AD choice towards a drug that is effective for those symptoms, such as OCD benefiting from an SSRI or clomipramine . Comorbid bulimia nervosa may benefit from SSRIs and anorexia nervosa by use of an AD that promotes weight gain. Substance use disorders occurring in the context of depression may affect AD choice; for example, if smoking cessation is a goal, bupropion should be considered, owing to its effects on reducing nicotine craving .…”
Section: Resultsmentioning
confidence: 99%
“…Presence of a comorbid anxiety disorder may weight AD choice towards a drug that is effective for those symptoms, such as OCD benefiting from an SSRI or clomipramine . Comorbid bulimia nervosa may benefit from SSRIs and anorexia nervosa by use of an AD that promotes weight gain. Substance use disorders occurring in the context of depression may affect AD choice; for example, if smoking cessation is a goal, bupropion should be considered, owing to its effects on reducing nicotine craving .…”
Section: Resultsmentioning
confidence: 99%
“…SSRIs have demonstrated to be useful treatment options for bulimia nervosa (BN) and binge eating disorder (BED) [30]. Fluoxetine is the only SSRI with FDA approval for BN, though other SSRIs have shown effectiveness [30][31][32]. In BED, a meta-analysis of 45 studies showed SSRIs provided some improvement in remission and reduction in the frequency of binge eating but no improvement in patient BMI [33].…”
Section: Eating Disordersmentioning
confidence: 99%
“…Given the potential risks of stimulants in BN, an RCT would ideally examine whether a stimulant has advantages over other available medications with proven safety profiles. For example, fluoxetine (60 mg/day dosage) has regulatory approval as a treatment for BN based on efficacy and a very good safety profile in both short‐ and long‐term trials (Bello & Yeomans, 2018). Therefore, it would be sensible to compare a stimulant to fluoxetine (60 mg/day dosage), to assess whether a stimulant is more efficacious than fluoxetine.…”
Section: Future Directions For Researchmentioning
confidence: 99%